Análise da imunoexpressão do TGF-β1 e BMP-2 no desenvolvimento craniofacial e femoral de ratos neonatos tratados e não tratados com alendronato - Vieira, Juliana de Souza (2017)
Little is known about the effects of alendronate during bone development in neonatal period. Some studies show that drug interfering in bone growth factors, favoring the development of this tissue. Supported by this premise, the objective of this study, is verify the immunoexpression of TGF-β1 and BMP-2 in maxillary and femoral bone development in specimes that received alendronate. Sixty neonatal rats were used, 30 of them received the administration via intraperitoneal of Alendronate 1mg/kg/daily, while the other rats constitutes the control group (received saline solution). After 2, 7 and 12 day after birthday the rats were euthanatized and the femur and skull was collected to histological and immunohistochemical analysis of expression of TGF-1and BMP-2 and histological analyses. On skull in group Aln with 7 days of life it was possible to observe fusion on the secondary palate, in the whole group, however, a fusion interface area of the primary palate remained open in both groups. In addition, a presence of bone matrix deposition was more dense when compared to the control. These results coincided with higher immunoexpression of TGF-β1 and BMP-2. On day 12, both group ,C and Aln, presented fusion of the secondary palate. However, the primary palate remained open. The control group presented greater mineralization in this anatomical area due to a smaller endochondral expansion. In the femur on day 2, there was difference between group C and Aln. group C , the entire cartilage area exhibited positivity to TGF-β1, whereas a BMP-2 was positive for the recently produced peripheral trabecular bone. In the Aln group TGF-β1 was expressed in some sites of neoformed trabecular bone, peripherally to the bone marrow area. BMP-2, unusually, was positive in proliferative and hypertrophic chondrocytes. On day 12, as immunohistochemical characteristics, as well as histological characteristics of group C, were similar to group C with 2 days. Differently, all as chondrocyte layers, positively exhibited a BMP-2 in specimens receiving alendronate promoting atypical and irregular endochondral deposition, minimizing chondroblastic expansion. The newly formed bone also showed to be different at 12 days in the Aln group. Within the limits of the present study, it was possible to conclude: In palate the alendronate only accelerated the closure of the secondary palate, and not mineralization between the primary palate. In the femoral area, alendronate produced atypical bone formation with serial cartilage, prompting that this drug may compromise the growth zone of the long bones.